2015
DOI: 10.1007/s11920-015-0605-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprogression and Cognitive Functioning in Bipolar Disorder: A Systematic Review

Abstract: Bipolar disorder (BD) has been associated with impairments in a range of cognitive domains including attention, verbal learning, and mental flexibility. These deficits are increased during the acute phases of the illness and worsen over the course of BD. This review will examine the literature in relation to potential mechanisms associated with cognitive decline in BD. Scopus (all databases), Pubmed, and Ovid Medline were systematically searched with no language or year restrictions, up to January 2015, for hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(88 citation statements)
references
References 74 publications
6
77
3
2
Order By: Relevance
“…Thus, aging is associated with a disruption and weakening of the coordinated activity between the anterior and posterior components of the DMN. A similar observation in our sample of BD patients hints at the possibility that BD may be associated with an underlying accelerated aging process (Cardoso, Bauer, Meyer, Kapczinski, & Soares, 2015; Rizzo et al, 2014). Although overall connectivity strength was preserved, reduced variability may be an early sign of age-related changes that precedes further disruption of these networks, contributing to cognitive decline.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, aging is associated with a disruption and weakening of the coordinated activity between the anterior and posterior components of the DMN. A similar observation in our sample of BD patients hints at the possibility that BD may be associated with an underlying accelerated aging process (Cardoso, Bauer, Meyer, Kapczinski, & Soares, 2015; Rizzo et al, 2014). Although overall connectivity strength was preserved, reduced variability may be an early sign of age-related changes that precedes further disruption of these networks, contributing to cognitive decline.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, while we had a great deal of information about our participants, including age of BD illness onset and assessment for psychopathology, mood, and functioning at the time of CANTAB testing, we did not have prospective information for the child BD participants about number and duration of mood episodes prior to testing. Given that some, but not all studies suggest that clinical course influences cognitive performance, further work is needed using longitudinal studies assessing both psychopathology and cognitive performance (Cardoso et al, 2015; Dickstein et al, 2015a). Our lack of age effects or age-diagnosis interactions could also stem from cohort differences between our younger participants with BD and our older participants with BD.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that young and older adults with BD have significant cognitive impairment, especially with executive function and attentional processing, compared to age-matched control participants (2,3). The presence of cognitive impairment has been associated with greater disability, and it has been proposed that cognitive impairment may be a marker of neuroprogression (that is, a progressive condition that leads to cognitive impairment and dementia) in BD patients (4,5). Nonetheless, recent longitudinal studies do not corroborate this view since they failed to demonstrate accelerated cognitive decline in BD compared to age-matched controls, despite the fact that persons with BD performed worse than control participants at all study assessment points (6,7).…”
Section: Introductionmentioning
confidence: 99%